2020
DOI: 10.3897/phytokeys.160.54237
|View full text |Cite
|
Sign up to set email alerts
|

The rediscovery of Uraria lacei Craib (Leguminosae) after 67 years from India

Abstract: Manipur is one of the biodiversity-rich states in the North-Eastern region of India, and it is also part of the Indo-Burma biodiversity hotspot with rich plant diversity and endemism. Recent field exploration in the area has resulted in the rediscovery of Uraria lacei Craib after 67 years from its last collection in 1952. The rediscovery of this beautiful species fills a gap in the current distribution knowledge and should pave the way for its immediate conservation and propagation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Field studies were carried out in six states of Northeast India: Arunachal Pradesh, Assam, Manipur, Meghalaya, Mizoram and Nagaland, during 2018 and 2019. Specimens of U. lacei were rediscovered after 67 years from Manipur, India (Gogoi & Rana 2020). The distribution map was generated using QGIS 3.18.1-Zürich (Map 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Field studies were carried out in six states of Northeast India: Arunachal Pradesh, Assam, Manipur, Meghalaya, Mizoram and Nagaland, during 2018 and 2019. Specimens of U. lacei were rediscovered after 67 years from Manipur, India (Gogoi & Rana 2020). The distribution map was generated using QGIS 3.18.1-Zürich (Map 1).…”
Section: Methodsmentioning
confidence: 99%
“…The climate and topography of both phytogeographic Uraria lacei Craib (1910: 276) NOTES. The description provided in Gogoi & Rana (2020) for Uraria lacei does not include the characters of U. pulchra. TYPIFICATION.…”
Section: Taxonomic Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Uraria paniculata C.B.Clarke is a synonym of U. lacei Craib. Uraria lacei is rare and was only recently rediscovered after 68 years from Manipur, India (Gogoi & Rana, 2020) and is in dire need of conservation. During the taxonomic revision of the genus Uraria in India, we observed that the names, U. prunellifolia and U. paniculata still need lectotypification.…”
Section: ■ Introductionmentioning
confidence: 99%